Stenting the arterial duct: Practical aspects and review of outcomes - Buys, D.G.; Brown, S.C.; Greig, C. (SA Heart Journal, 2017)
Cyanotic congenital heart lesions with duct-dependent pulmonary blood fl ow often require early intervention. Surgical palliation remains the treatment of choice, but is associated with substantial morbidity and mortality. Ductal stent implantation is becoming a recognised alternative to maintain pulmonary blood fl ow. Results of ductal stenting have improved and outcomes are good. We discuss the outcomes of published data and the practical aspects of ductal stenting.